Prediction model of dengue hemorrhagic fever transmission to enhance early warning system in Gergunung Village, Klaten District, Central Java - Satoto, Tri Baskoro Tunggul; Dwiputro, Alfin Harjuno; Risdwiyanto, Rifa Nadhifa; Hakim, A. Ulil Fadli; Pascawati, Nur Alvira; Diptyanusa, Ajib (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
The dengue virus that causes dengue hemorrhagic fever (DHF) in principle is transmitted to humans through the bites of Aedes sp. In Indonesia, the disease is endemic in most provinces, including in Gergunung Village in Klaten District, Central Java. The village has shown the highest incidence of DHF for the last 5 years. Changes in demographical conditions, environment, and climate condition are predictors of dengue fever. This study aimed to demonstrate the association among human behavioral variables, physical environmental factors, and climate elements with DHF transmission to develop active surveillance model of DHF outbreak by the analysis of potential predictors. The research was an observational analytic study with case control design. Study population was selected from households with DHF case in 2016 through 2017 and the controls with ratio of 1:2. In total, 34 households were labeled as case and 68 households were labeled as control. Data collection was performed by observations, direct measurements, and interviews. Data were analyzed using appropriate statistical analysis with probability value of p<0.05. The result showed that insecticide use, proper waste management, livestock breeding, presence of plastered floor, water-resistant walls, bedroom windows, doors, gutters, and open drainage system, all did not show association with DHF case occurrence (p>0.05). In contrast, houses closer to each other tended to have more DHF cases (p<0.05; OR: 2.96; 95% CI: 1.01–8.67). Physical environmental factors and climate elements did not demonstrate significant associations with DHF case occurrence in this study. Human behavioral variables, physical environmental factors, and climate elements may serve as potential predictors of DHF outbreak, hence should be put into the model to enhance early warning system.